รูปแบบการดำเนินชีวิต พฤติกรรมการบริโภค และการเปิดรับสื่อของชายรักชายในเขตกรุงเทพมหานคร - เรข์ณพัศ ภาสกรณ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2011)
To study lifestyles, purchasing behavior and media exposure of male homosexual in Bangkok. Questionnaires were used to collect data from a total of 400 gays in Bangkok.Descriptive analysis, Factor analysis and Pearson’s product moment correlation coefficients were used to analyze data through SPSS for Windows. Results of the research are as follows : 1. Bangkok gays are categorized into 7 lifestyles namely Traveled Gay Lifestyle, Gorgeous Gay Lifestyle, Progress Gay Lifestyle, Hi-Technology Gay Lifestyle, Online Gay Lifestyle, Thai-Cherish Gay Lifestyle and Sweet-Home Gay Lifestyle. 2. In terms of consuming behavior, gays in Bangkok highly expend on fashion and entertainment items. 3. Bangkok Gays highly expose to media, which are Internet, Television and radio. For the gay media which were exposed most are Person media, Internet and mass media.